Analisis Performa Keuangan Pemerintah Kota Surakarta - Lucy Grace Ariestha Manurung; Rosalin Putri Lubis Putri Lubis; Agus Munandar (Coopetition : Jurnal Ilmiah Manajemen, 2023)
Financial reporting is the financial condition of a certain area in a periode that contains the actual use of funds. This research was conducted with the aim of analyzing the relationship between the management and financial realization of the Surakarta City Government from 2017-2021. This analysis uses several ratios, namely the ratio of decentralization, the level of independence, the level of effectiveness, and the level of efficiency. The result of the analysis that has been carried out is that the average degree of decentralization in Surakarta is 10,6% and has fluctuated. The Surakarta government has a fairly good level of independence in managing finances and has increased every year. The ability to manage finances owned by the Surakarta Government is good with an effective level of effectiveness, but it has decreased quite drastically, name 13,29% in 2021. From the results of the analysis, it can also be seen that the efficiency level is still below 60% in the very low category.